The burden perceived by informal caregivers of the elderly in Saudi Arabia - Sulaiman A Alshammari (Journal of Family and Community Medicine, 2017)
OBJECTIVES: The objective of this study was to discover the characteristics of informal caregivers of elderly patients; to determine the socioeconomic, psychological, and physical consequences facing informal caregivers; and to measure their burdens and needs. MATERIALS AND METHODS: This study was a cross-sectional survey of informal caregivers of elderly patients. Participants were recruited from different hospitals and primary care clinics in Riyadh, Saudi Arabia. For an intended sample size of 384 caregivers, a multistage sampling was used. A self-administered questionnaire was used to collect data. Data analysis included student's t-test and ANOVA to test for statistical significance. RESULTS: The study included 315 caregivers of elderly patients. Over half of the elderly patients were female (55.9%) and over 70 years old (65.7%); about 31% had chronic diseases or disabilities, which represented the majority of health problems reported by the elderly population. Most of the caregivers were family members (87.9%), young (43.8%), female (52.7%), unemployed (54.6%), and unmarried (58.1%). Most caregivers suffered from musculoskeletal problems (78.1%). The mean Zarit Burden Interview score was 31.3, which indicated a moderate burden. More than half of caregivers requested blood pressure (55.6%) and blood sugar measuring devices (53%). Three quarters (74.9%) of the caregivers wanted educational training to cope with emergencies. Most caregivers expressed a need for frequent healthcare for themselves (58.4%) and a home health visit service (72.9%) to support them in the care of their elderly. CONCLUSIONS AND RECOMMENDATIONS: Mobilization of resources in locations where these carers of the elderly live are greatly needed. In addition, health authorities should provide devices and essential training to manage the common problems and emergencies that informal caregivers have to deal with. Moreover, caregivers need follow-up supervision by a home visit team. Further studies are required to guide the implementation of the above advice.